(untitled) (World Science, 2021)
The processes of information support of situational management of infocommunication networks in the conditions of influence of external disturbances are considered in the work. The expediency of using the mathematical apparatus of information theory for the analysis of processes of control of parameters of infocommunication networks is substantiated. It is shown that periodic multiple sequential control of the parameters of the infocommunication network provides determination of the state of the network under the influence of external interference and the probability of its transition to a new state in the near future. The entropy of the controlled process changes with changing quantization step and multiple successive measurements. It is noted that in the case of periodic multiple consecutive control, the object is constantly in transition in terms of information. The entropy value of an object can be considered determined only for some short periods of time between measurements or when information about the object is not received. An important condition for improving the quality of control is to reduce and completely eliminate delays in the information process.